Transformation of Character Education Based on THK for Elementary School Students in the Digital Era - Sumarjono, Kadek Jefry Dwi; Ariyana, Komang Agus; Riani, Luh; Yasa, I Gede Windu; Lesmana, Kadek Yogi Parta (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This study aims to determine the meaning of Character Education, Tri Hita Karana, Digitalization, and the transformation of character education based on Tri Hita Karana in elementary schools in the digital era. The meaning of Education. Education "is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual religious strength, self-control, personality, intelligence, noble morals and skills needed by themselves, society, nation and state" (Law No. 20 of 2003) ". This study uses a descriptive qualitative method. This study applies secondary data, where this data is obtained from various sources in the form of books and journals that are still related to the title of the study, because this type of research is a literature study. The researcher will describe and explain in detail the meaning of Character Education, Tri Hita Karana, Digitalization, and the transformation of character education based on Tri Hita Karana in elementary schools in the digital era. Character education based on Tri Hita Karana is a relevant approach and is very much needed in forming good student personalities in the digital era. By utilizing technology wisely and integrating spiritual, social, and environmental values, students can be taught to live in harmony with God, others, and the environment. Therefore, it is important for educators to create a learning environment that prioritizes a balance between character values and the use of technology in order to form a generation that is intelligent, well-mannered, and cares about others and the environment.